Evaluation of Growth and Yield Traits of Different Genotypes of Chickpea (Cicer arietinum L.) - Singh, Rashi; Mishra, S. N.; Pandey, Mudit (International Journal of Economic Plants, 2025)
The research was carried out during rabi (November, 2024–February, 2025) 2024–25 at Prof. Rajendra Singh (Rajju Bhaiya) university, Naini, Prayagraj to evaluate the yield and quality traits of five chickpea genotypes viz. PUSA 362, DNA334, Avrodhi, Himmat and Radhe .The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. Each genotype was sown in plots of 2×2 m2 size, with a row spacing of 30 cm and plant spacing of 10 cm. The crop was cultivated following recommended agronomic practices, including fertilization, irrigation, and pest management. The genotypes were assessed for various parameters, including plant height in cm, no. of branches, no. of pods plant-1, seed yield (g) plant-1, Seed yield plot-1, seed yield q ha-1 and resistance to diseases. The data collected were subjected to analysis of variance (ANOVA) to determine significant differences among genotypes. The analysis was performed using statistical software. Significant variations were observed among the genotypes for most traits, indicating substantial genetic diversity. The results of this study provided valuable insights into the performance of these genotypes under specific environmental conditions, enabling breeders and farmers to select high-yielding and quality chickpea varieties for improved productivity and nutritional value.